2018
DOI: 10.1007/s10897-018-0297-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Decisions: Perspectives of Active and Athletic Individuals with Inherited Heart Disease Who Exercise Against Recommendations

Abstract: Individuals with hypertrophic cardiomyopathy (HCM) and long QT syndrome (LQTS) are advised to avoid certain forms of exercise to reduce their risk of sudden death. Cardiovascular genetic counselors facilitate both adaptation to, and decision-making about, these exercise recommendations. This study describes decision-making and experiences of active adults who exercise above physicians' recommendations. Purposive sampling was used to select adults with HCM and LQTS who self-identified as exercising above recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Having friends and family participate with them in lower-intensity exercise was identified as something that helped them cope with the restrictions. A qualitative study explored perspectives of individuals with HCM and LQTS who continue to exercise against current recommendations and found many did make important modifications to their exercise program over time (Subas et al 2019). The value of a shared decision-making model in which the athlete's preferences are considered may be beneficial to addressing exercise restrictions.…”
Section: Sports Restrictionsmentioning
confidence: 99%
“…Having friends and family participate with them in lower-intensity exercise was identified as something that helped them cope with the restrictions. A qualitative study explored perspectives of individuals with HCM and LQTS who continue to exercise against current recommendations and found many did make important modifications to their exercise program over time (Subas et al 2019). The value of a shared decision-making model in which the athlete's preferences are considered may be beneficial to addressing exercise restrictions.…”
Section: Sports Restrictionsmentioning
confidence: 99%
“…This was surprising because those who are particularly athletic are often considered more likely to be nonadherent with exercise guidelines, therefore we hypothesized they may be less likely to be engaged in SDM. 7 Perhaps most impactfully, we found that higher levels of SDM were associated with lower decisional conflict and decisional regret. This is important because DCS and DRS scores were relatively high and both have been associated with poor psychosocial and medical outcomes.…”
Section: Discussionmentioning
confidence: 60%
“…Many of those diagnosed with ARVC are highly active individuals for whom exercise restriction may be particularly challenging. 7,8 In recognition of this complexity, guidelines recommend that exercise decisions for those with or at risk for ARVC follow a shared decision-making (SDM) model. 6 SDM is an increasingly popular model in medicine that aims to increase patient autonomy and engagement in medical decision-making.…”
mentioning
confidence: 99%
“…This is achieved primarily through the development and computation of genomic risk scores (GRSs) [15,16], which enhance precision, efficacy, and predictability concerning potential diseases. Identifying individuals at heightened risk for prevalent chronic diseases paves the way for targeted preventive measures, such as increased health monitoring, early therapeutic interventions, lifestyle modifications [17,18], and specialized diagnostic procedures. Furthermore, when combined with risk scores, genetic data can predict a patient's response to therapy and potential side effects from certain medications.…”
Section: Advancements and Applications Of Genetics In Cardiovascular ...mentioning
confidence: 99%